Comparative transcriptome analysis of bull X- and Y-spermatozoa - Sofi Imran Ul Umar; Sushil Prasad; Soumen Naskar; Pranab Jyoti Das; Mridula Sharma; Arunava Pattanayak; Dhanu Kumar Murasing; Vijai Pal Bhadana; Sujay Rakshit (Scientific Reports)
Abstract Sex-sorted bovine semen is a major breakthrough in the dairy sector. The current flow cytometer-based technology for sex-sorting of bovine semen is proprietary, slow, expensive, and associated with lower conception rates. Therefore, developing alternative technologies is crucial for advancing milk production globally through use of sexed semen. However, lack of a comprehensive omics dataset hinders the ability to comprehend significant differences between the sorted sperm types and develop robust biomarkers for sex-sorting. Here, we reported the RNA-Seq analysis of unsorted, X- and Y-sperm in Bos indicus cattle. The differential gene expression analysis revealed significant upregulation of 47 genes in bovine Y-sperm and downregulation of 20 genes in comparison to X-sperm (adjusted p value < 0.05). Sixteen percent of the transcripts were unique to X-sperm, whereas 20.7% were unique to Y-sperm. The top 22 differentially expressed genes (DEGs) were validated using qPCR. A significant up- or down-regulation was detected in 21 of the 22 genes when comparing bovine Y-sperm to X-sperm (p < 0.01 and p < 0.05). The transcriptome dataset, the first in the league of bovine X- and Y-sperm, will aid in biomarker discovery for sex-sorting of bovine semen and improved fertility outcomes.